A New Method for DNA Isolation from Bone Marrow & Sperms of White Mice - Ahmed, Shayma J. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: A quick and easy method was developed for extraction of DNA of eukaryotes from different samples, which are bone marrow and sperms in white mice Mus musculus strain (Balb/c).Patients and Methods: this method using high salt buffer, Ethylene diemine tetracetec acid (EDTA), Trypsine,Sodium Dodecyl Sulfate(SDS), and urea without using Proteinase-K digestion or ultracentrifugation.Results: This method was successful in extracting DNA from different samples in eukaryotic and this DNA is suitable for Hind III digestion.Conclusion: Without further clean-up, the extracted DNA can be used for restriction endonuclease digestion or for numerous applications.